Reflection On Anglicism: From Jargonizing To Popularising Speaking In Reshaping The Language Landscape Within The Algerian Society - Nadira Chahboub; Ali Belaidi (The Journal of Studies in Language, Culture and Society)
Our paper suggests reflecting on the Anglicism process and its impact on educational standards. Despite the complexity of the Algerian linguistic landscape, political decisions have only added further complications, affecting everyday communication and reshaping social culture. Since the process was launched, many gaps and serious considerations have emerged. As a result, the linguistic landscape has changed since the operation was carried out. Regarding the methodological aspect, our paper is an exploratory and reflective study that employs comparative analysis of various language studies exploring the relationship between language, society, power, and knowledge. Additionally, it integrates interdisciplinary perspectives to communicate the political implications of Anglicism, tracing its impact from the University to society. Our article evaluates this decision from multiple perspectives and anticipates how it may reshape society at various levels. It finally comes to the following conclusions: the Algerian linguistic landscape has drastically changed in Algerian society from the top to the bottom, and it is changing. The actual change will narrow the presence of the French language starting from everyday life to other contexts, but most importantly the professional sphere where the French language is more used. Our paper aims to comprehensively understand the common ground among the four languages used in Algeria. Additionally, it seeks to encourage researchers to conduct genuine scientific research on integrating the English language, whether at the university level or within the educational system.